Posterior polymorphous corneal dystrophy in Czech families maps to chromosome 20 and excludes the VSX1 gene - Gwilliam, Rhian; Liskova, Petra; Filipec, Martin; Kmoch, Stanislav; Jirsova, Katerina; Huckle, Elizabeth J; Stables, Catherine L; Bhattacharya, Shomi S; Hardcastle, Alison J; Deloukas, Panos; Ebenezer, Neil D (Investigative ophthalmology & visual science, 2005)
PURPOSE: Posterior polymorphous corneal dystrophy (PPCD) is an autosomal dominant disorder, affecting both the corneal endothelium and Descemet's membrane. In the Czech Republic, PPCD is one of the most prevalent corneal dystrophies. The purpose of this study was to determine the chromosomal locus of PPCD in two large Czech families, by using linkage analysis. METHODS: Linkage analysis was performed on 52 members of two Czech families with PPCD and polymorphic microsatellite markers and lod scores were calculated. The candidate gene VSX1 was also screened for mutations. RESULTS: Significant lod scores were obtained with microsatellite markers on chromosome 20. Linkage analysis delineated the Czech PPCD locus to a 2.7-cM locus on chromosome 20, region p11.2, between flanking markers D20S48 and D20S139, which excluded VSX1 as the disease-causing gene in both families. In addition, the exclusion of VSX1 was confirmed by sequence analysis. CONCLUSIONS: This study reports the localization of PPCD in patients of Czech origin to chromosome 20 at p11.2. Linkage data and sequence analysis exclude VSX1 as causative of PPCD in two Czech families. This refined locus for PPCD overlaps the congenital hereditary endothelial dystrophy (CHED1) disease interval, and it is possible that these corneal dystrophies are allelic.
Keywords: Descemetova membrána; Genetic Markers; Descemet Membrane; lokus kvantitativního znaku; Lod Score; Corneal Dystrophies, Hereditary; Homeodomain Proteins; Česká republika; mužské pohlaví; rodokmen; Pedigree; rohovkový endotel; oční proteiny; Czech Republic; dědičné dystrofie rohovky; Quantitative Trait Loci; Lod skóre; Eye Proteins; ženské pohlaví; Humans; mapování chromozomů; lidské chromozomy, pár 20; Chromosomes, Human, Pair 20; Endothelium, Corneal; Chromosome Mapping; Female; genetické markery; homeodoménové proteiny; lidé; Male